La danza folclórica montubia y el fortalecimiento del turismo cultural en la Provincia de Los Ríos - Alvarez Bajaña, Bryan Francisco (2022)
The present investigation defines he importance of the Montubia folk dance for the strengthening of cultural tourism in the province of Los Ríos, the folk dance comes from the coastal afrea. The gallop is a dance that is done in various parts of the coast, being an ancient tradition, of values customs, and ancestral knowled that has been replaced over time by the various modern occupations, there is Little interest in rescuing this dance that is part of the Montubia ethnic group of the los Ríos Province One of the common causes on the part of the different competent authority id the lack of interest in promoting cultural dances. Through thos research, the main vision is to determine the cultural potential, analyzing the creation of a web page to promate this type of artistic manifestation, so that people discover the cultural contribution of this beautiful province Through social networks and other online tools, the Montubia folk dance can be spread, creating ner strategoes and offering exclusive experiences, therefore, it Will be posible to have a greater influx of local tourists and Nations, making it Known that dance and amorphous people are a cultural expresion of this land of Rio de janeiro, thus being a tourit element for the other province of Ecuador, putting into practice the rescue of traditions and customs, increasing cultural tourism considered alternative tourism. It should be noted that with this case analysis, the main befeciaries are the community, having the knowledge about the conservation of their Montubio identity, in the same way this generates a motivation for the authorities who are responsible for investing more in cultural tourism.